Engineered Living Oriented Electrospun Fibers Regulate Stem Cell Para‐Secretion and Differentiation to Promote Spinal Cord Repair. Issue 9 (10th January 2023) - Xu, Jingzhi; Xi, Kun; Tang, Jincheng; Wang, Juan; Tang, Yunkai; Wu, Liang; Xu, Yichang; Xu, Zonghan; Chen, Liang; Cui, Wenguo; Gu, Yong
Abstract: Living biomaterials directly couple with live cells to synthesize functional molecules and respond to dynamic environments, allowing the design, construction and application of next generation composite materials. Improving the coordination and communication between artificial materials and living cells is essential. In this study, collagen self‐assembly and micro‐sol electrospinning techniques are used to prepare oriented living fiber bundles that can increase the transplantation rate of stem cells in the early stages of inflammation, indirectly enhancing the dynamic regulation of stem cells during inflammation. Additionally, brain‐derived neurotrophic factor (BDNF) contained in the fiber can improve the differentiation of bone marrow mesenchymal stem cells (BMSCs) into neurons once the inflammatory storm subsides. The living oriented fiber bundles fully simulate the 3D structure of the central nervous system, activate integrin β 1, promote the growth and adhesion of stem cells in the acute stage of inflammation, upregulate anti‐inflammatory genes by more than twofold via BMSCs in response to inflammation, and stably release BDNF for up to 4 weeks post‐inflammation storm subsidence. Finally, the BDNF induces the differentiation of BMSCs to neurons by enhancing the expression of neural‐related genes, which enables the recovery of neurological functions in the later stages of spinal cord injury. Abstract : Living biomaterials are composite materials that combine both active and inactive components. Collagen self‐assembly and micro‐sol electrospinning techniques are used to prepare oriented living fiber bundles that increase the transplantation rate of stem cells in inflammation stages, indirectly enhancing the dynamic regulation of stem cells. Improving the coordination and communication between artificial materials and living cells is essential.